Classification of Polymeric Insulating Surface Condition Based on Leakage Current Total Waveform Distortion - AMAN, AMINUDIN (2012)
Leakage current waveform and its frequency component are frequently used as a diagnostic tool to identify the state of polymeric condition and its contamination level. This paper presents a new analysis approach of leakage currents on polymeric high voltage insulation material as well as its surface condition. This leakage current has been monitored and captured with accelerated aging laboratory –inclined plane tests. Previously, Fast Fourier Transform method was used for leakage current parameters estimation, but it has a limitation of being only suitable for stationary signal. To overcome this, the linear time-frequency distribution technique is used, and spectrogram is implemented for the time-frequency representation. The aim of this technique is to extract all relevant information from leakage current signal, and then leakage current parameters are estimated to indentify its characteristics. These include root mean square current, fundamental root mean square current and total current waveform distortion. This proposed approach, will cater all the frequencies components of the leakage current signal like its total current harmonics and total current inter-harmonics distortions as well as giving information for the total current waveform distortion. It was shown that instantaneous root mean square current per unit value and total current waveform distortion % are useful to reveal the polymeric insulating surface condition. Referring to rules based value, the classification of material surface state could be determined instantaneously.